Protocol for diaphragm pacing in patients with respiratory muscle weakness due to motor neurone disease (DiPALS): a randomised controlled trial - McDermott Christopher J (BMC Neurology, 2012)
Abstract Background Motor neurone disease (MND) is a devastating illness which leads to muscle weakness and death, usually within 2-3 years of symptom onset. Respiratory insufficiency is a common cause of morbidity, particularly in later stages of MND and respiratory complications are the leading cause of mortality in MND patients. Non Invasive Ventilation (NIV) is the current standard therapy to manage respiratory insufficiency. Some MND patients however do not tolerate NIV due to a number of issues including mask interface problems and claustrophobia. In those that do tolerate NIV, eventually respiratory muscle weakness will progress to a point at which intermittent/overnight NIV is ineffective. The NeuRx RA/4 Diaphragm Pacing System was originally developed for patients with respiratory insufficiency and diaphragm paralysis secondary to stable high spinal cord injuries. The DiPALS study will assess the effect of diaphragm pacing (DP) when used to treat patients with MND and respiratory insufficiency. Method/Design 108 patients will be recruited to the study at 5 sites in the UK. Patients will be randomised to either receive NIV (current standard care) or receive DP in addition to NIV. Study participants will be required to complete outcome measures at 5 follow up time points (2, 3, 6, 9 and 12 months) plus an additional surgery and 1 week post operative visit for those in the DP group. 12 patients (and their carers) from the DP group will also be asked to complete 2 qualitative interviews. Discussion The primary objective of this trial will be to evaluate the effect of Diaphragm Pacing (DP) on survival over the study duration in patients with MND with respiratory muscle weakness. The project is funded by the National Institute for Health Research, Health Technology Assessment (HTA) Programme (project number 09/55/33) and the Motor Neurone Disease Association and the Henry Smith Charity. Trial Registration: Current controlled trials ISRCTN53817913. The views and opinions expressed therein are those of the authors and do not necessarily reflect those of the HTA programme, NIHR, NHS or the Department of Health.